2013
DOI: 10.1037/a0029128
|View full text |Cite
|
Sign up to set email alerts
|

Why am I remembering this now? Predicting the occurrence of involuntary (spontaneous) episodic memories.

Abstract: Involuntary episodic memories are memories of events that come to mind spontaneously -that is, with no preceding retrieval attempts. They are common in daily life and observed in a range of clinical disorders in the form of negative, intrusive recollections or flashbacks. However, little is known about their underlying mechanisms. Here we report a series of experiments in which-for the first time-the activation of involuntary memories are controlled and predicted on the basis of manipulations done at encoding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
182
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(211 citation statements)
references
References 66 publications
23
182
0
Order By: Relevance
“…Berntsen, Staugaard, & Sørensen, 2013). For example, increasing the positive affect generated while imagining a scenario during the training may increase the chance that the image later returns as a positive involuntary memory (e.g.…”
Section: Clinical Practices and Summarymentioning
confidence: 99%
“…Berntsen, Staugaard, & Sørensen, 2013). For example, increasing the positive affect generated while imagining a scenario during the training may increase the chance that the image later returns as a positive involuntary memory (e.g.…”
Section: Clinical Practices and Summarymentioning
confidence: 99%
“…One possibility is that cues are more likely to elicit future MTT when they interact with current goal states or that a certain level of cue discriminability is needed . However, further experimentation is required to examine these possibilities (see Schlagman & Kvavilashvili, 2008, for arguments concerning how cues and memory interact in involuntary past MTT; see Berntsen et al, 2013, for manipulations of cueing in relation to activating involuntary episodic memories). Another, but related, question concerns the role of unconscious processes in involuntary future thinking; specifically, the extent to which they are primed by previous thoughts or goals (see Szpunar, 2010).…”
Section: Future Directionsmentioning
confidence: 99%
“…Anderson et al, 2011;Hintzman, 2011;Kelley & Jacoby, 2000;SteMarie & Jacoby, 1993). Although several studies have induced involuntary autobiographical memories using laboratory techniques (Ball, 2007;Berntsen, Staugaard, & Sørensen, 2013;Schlagman & Kvavilashvili, 2008;Uzer, Lee, & Brown, 2012), to our knowledge, this is the first study to use a laboratory paradigm to examine past and future events that are retrieved voluntarily and involuntarily. In so doing, we attempt to fulfil two aims: (1) to validate a new laboratory method of involuntary MTT and (2) to understand the emotional, representational, and cognitive characteristics of these four mental representation types, especially the phenomenon of involuntary future MTT, which has hitherto been studied using naturalistic methods.…”
mentioning
confidence: 99%
“…In the General Discussion, we describe the widespread importance of remindings and discuss results suggestive of large individual differences in the likelihood of looking back, along with the potential importance of those individual differences. Berntsen, Staugaard, and Sørensen (2013) provided an excellent review of research revealing spontaneous episodic remembering, and they reported results to contrast voluntary with spontaneous remembering. Spontaneous remembering was described as being faster and more dependent on stimulus control than is voluntary memory.…”
mentioning
confidence: 99%